The Effectiveness of a Blended Learning-Based Parenting Program Model in Enhancing Parents' Child-Rearing Competence - Fauziah, Puji Yanti; Aryani, Neng Desi; Wijayanto, Arif; Azzahra, Isti Tho'ah; Ningsih, Widiya; Raihani, Yasmina Nur (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to analyze the effectiveness of a blended learning-based parenting model in enhancing parents’ understanding and involvement in a nonformal early childhood education setting. This study employed a descriptive quantitative approach using a one-group pre-test and post-test design. The research population consisted of parents and educators at nonformal early childhood education institutions in Cianjur Regency, Indonesia, with the study specifically conducted at PAUD Al Faqih. A sample of 25 active participants in the parenting program was selected using purposive sampling. Data were collected through questionnaires and documentation, then analyzed using descriptive statistical techniques. The results indicate that the blended learning–based parenting model achieved a feasibility score of 4.2, categorized as feasible. Furthermore, post-test findings demonstrate a substantial improvement in parents’ understanding of positive parenting practices, effective communication, and their roles as primary educators for their children. These findings suggest that the blended learning–based parenting model is effective as an alternative strategy for strengthening parental involvement in nonformal early childhood education.